ANALYSIS OF PHYSICAL ACTIVITY TO IMPROVE STUDENTS BASIC MOVEMENT SKILLS PHYSICAL LITERACY BASED PRIMARY SCHOOL - Ardiana , Pradipta Ahdha (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
Abstract This literature review study is based on this The current education pattern cannot accommodate the needs of each individual to grow optimally. Most current education patterns do not provide enough space for students' uniqueness in carrying out physical activities. Mastery of basic movements needs to be given to children in the form of physical activity. Physical activity that is designed needs to increase and stimulate children to move without compulsion. The physical activity provided can be in the form of Physical Literacy . The literature review method was carried out on three articles obtained from a number of databases, PubMed, EBSCO, and Springer Link. Keywords for searching articles are physical activity, physical literacy , basic movement skills, physical literacy . Researchers use